Foreign Trade and FDI in the Austrian Regions - A new methodology to estimate regional trade and an analysis of the crisis effects - Roman Römisch (FIW - Research Centre International Economics, 2012)
Foreign trade and foreign direct investments (FDI) are key elements for economic development and growth of both a country and its regions. This paper focuses on foreign trade and FDI in Austrian regions (Bundesländer). Unfortunately, data on regional trade in Austria is only available on a very limited basis. The aim of this study is to develop new methodologies for the estimation of exports and imports of Austrian regions and analyse the data generated by this methodology. The basic idea is to disaggregate national foreign trade data to the regional level by using national input-output, regional employment and other supplemental data. This allows estimating Austrian regional foreign trade for the years 1999 to 2009. The study shows a large variation in trade among regions. Lower Austria, Upper Austria, Styria and Vorarlberg are the regions with the highest export share. The importance of regional trade increases between 1999 and 2008; the crisis in 2009 had a strong negative impact. Furthermore, the competitiveness of regions differs considerably. Only three regions, Upper Austria, Styria and Vorarlberg, show trade surplus.
Keywords: C82; F10; F14; F16; R1; R12; R15; 330; Austria; regions; Bundesländer; foreign trade; economic crisis